Abrupt rise of end tidal carbon dioxide level was a specific but non-sensitive marker of return of spontaneous circulation in patient with out-of-hospital cardiac arrest. (July 2016) - Lui, Chun Tat; Poon, Kin Ming; Tsui, Kwok Leung
Abstract: Objective: To evaluate the diagnostic accuracy of an abrupt and sustained increase in end-tidal carbon dioxide (ETCO2 ) to indicate return of spontaneous circulation (ROSC) during resuscitation of patient with out-of-hospital cardiac arrest. Design: Cross-sectional study. Setting: Emergency department of two regional hospitals. Methods: Patients with age ≥18 years old, suffered non-traumatic out-of-hospital cardiac arrest with active resuscitation and endotracheal intubation performed in emergency department, were included. ETCO2 value was charted throughout resuscitation. Time of ROSC was remarked. ETCO2 levels before and after ROSC were compared. Diagnostic accuracy of ETCO2 rise ≥10 mmHg, ETCO2 rise ≥20 mmHg, and ETCO2 rise to the level ≥40 mmHg were evaluated for indicating ROSC. Results: ETCO2 level immediately after ROSC was higher as compared to the value before return of circulation (median ETCO2 was 32 mmHg and 41 mmHg respectively, p  = 0.033). With ETCO2 rise ≥10 mmHg, the sensitivity was low (33%, 95% CI 22–47%), while specificity was 97% (95% CI 91–99%). Positive and negative predictive values were 83% (95% CI 62–95%) and 74% (95% CI 66–81%) respectively. The diagnostic accuracy was higher in cardiac arrest with presumed non-cardiac etiology (sensitivity 45%, specificity 100%) as compared to those with cardiac etiology (sensitivity 18%, specificity 97%). Conclusions: The feature of an abrupt rise of ETCO2 was a specific but non-sensitive marker of ROSC in patient with out-of-hospital cardiac arrest.